Seafire - Parker, Natalie C. (Razorbill, 2018)
Follows Caledonia Styx, captain of her own ship, the Mors Navis, and its all-female crew as they strive to defeat the powerful fleet of Aric Athair, the vicious warlord who has taken their homes and families.